2019
DOI: 10.1021/acs.orglett.9b02519
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Michael/Dieckmann Cyclization Reaction of Alkynones To Construct Spirocyclopentene Oxindoles

Abstract: A highly enantioselective conjugate addition/ Dieckmann cyclization of 3-carboxymethyl substituted oxindoles with electron-deficient internal alkynes was achieved under the catalysis of a chiral guanidine catalyst and NaH. This protocol provides access to a wide range of synthetically useful optically active spirocyclopentenone oxindoles and their derivatives under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In 2019, Liu and co‐workers developed a strategy to give optically active spirocyclopentenone oxindoles 69 through a highly enantioselective conjugate addition/Dieckman cyclisation of 3‐carboxymethyl oxindoles 60 with electron‐deficient ynones 21 through chiral guanidine 68 catalysis (Scheme 21). [41] The enantioenriched spirocyclopentenone oxindoles 69 were obtained in excellent yields and enantioselectivity (70–99% yield and 86–99% ee). The bifunctional guanidine catalyst promotes enolate formation in 3‐substituted oxindole and activates alkynone electrophile through hydrogen bonding activation.…”
Section: Enantioselective Organocatalytic Reactions Of Conjugated Alk...mentioning
confidence: 96%
“…In 2019, Liu and co‐workers developed a strategy to give optically active spirocyclopentenone oxindoles 69 through a highly enantioselective conjugate addition/Dieckman cyclisation of 3‐carboxymethyl oxindoles 60 with electron‐deficient ynones 21 through chiral guanidine 68 catalysis (Scheme 21). [41] The enantioenriched spirocyclopentenone oxindoles 69 were obtained in excellent yields and enantioselectivity (70–99% yield and 86–99% ee). The bifunctional guanidine catalyst promotes enolate formation in 3‐substituted oxindole and activates alkynone electrophile through hydrogen bonding activation.…”
Section: Enantioselective Organocatalytic Reactions Of Conjugated Alk...mentioning
confidence: 96%
“…A noticeable decrease in the enantiomeric enrichment of the reaction product 229 (to 88 % ee), according to the tables of the authors in the article, is observed in two cases: when R 1 = Ph, R 2 = Pentyl, R 3 = H (70 % yield) and R 1 = R 2 = Ph, R 3 = I (93 % yield; Scheme 60). [252] The organocatalyzed asymmetric Mannich-type spirocyclization was employed to access the spiro[pyrrolidin-3,3'-oxindoles] 230 from 2-oxo-tryptophan methyl ester 231 and halogen-, methyl-or methoxybenzaldehydes 232. The nature of the organocatalysts and solvents used in carrying out these reactions strongly influence the stereoselectivity of cyclization.…”
Section: Synthesis Of 3-spiro-2-oxindoles From 3-alkyl-2-oxindole Dermentioning
confidence: 99%
“…A noticeable decrease in the enantiomeric enrichment of the reaction product 229 (to 88 % ee ), according to the tables of the authors in the article, is observed in two cases: when R 1 =Ph, R 2 =Pentyl, R 3 =H (70 % yield) and R 1 =R 2 =Ph, R 3 =I (93 % yield; Scheme 60). [252] …”
Section: Syntheses Of Spiroheterocycles From 3‐alkylidene‐indol‐2‐onementioning
confidence: 99%
“…Spiro-cyclopentadienes 3 could be easily transformed to spirocyclopenta [c]furan oxindoles 7 through a cascade reduction/ Paal−Knorr process (Scheme 3b). 12 To understand the mechanism of the (3 + 1 + 1) annulation, we tried to isolate and identify the reaction intermediate. The model reaction of 1a with 2a afforded diene (E,E)-8a and (Z,E)-8a in 66% total yield by quenching the reaction after 10 min (Scheme 4a).…”
mentioning
confidence: 98%
“…To verify the synthetic potential of our method, we explored the derivatization of products 3 . Spiro-cyclopentadienes 3 could be easily transformed to spiro-cyclopenta­[ c ]­furan oxindoles 7 through a cascade reduction/Paal–Knorr process (Scheme b) …”
mentioning
confidence: 99%